The heritage value in housing between sustainability and extinction The model of the city of Ouled DjellaL in Algeria - Djouima, Ahmed; Torkia, Assil (Journal of Architecture and environment of child, 2021)
Algerian cities hold many buildings that have special cultural and heritage significance that distinguish them and require their preservation. Accordingly, architects have adopted the principle of restoration as a mechanism for maintenance and preservation. However, with the development of concepts in the field, this concept gradually shifted from the concept of protection to the concept of sustainable preservation to include the process of maintaining the building with knowledge of the values related to it, its architectural texture and the features of its society. The bioclimatic housing complex, built in the eighties of the last century, in Ouled DJellal, southern Algeria, is one of the most important living architectural landmarks that attracts the interest of every researcher or visitor to this city. Despite the environmental design of traditional housing and energy conservation, the housing complex has been subject to several processes of change and transformation of its historical shape and its urban landscape under the pretext of the development of modern needs of the population. This architectural heritage was severely damaged, as it replaced parts of its organic tissue with new parts that isolated it and threatened its survival. This research follows an inductive description approach to highlight the importance of this model for sustainable environmental architecture. An analytical approach to monitor the drivers of intentional and unintentional changes by users is also used, to end up with a set of results and recommendations that would save what remains of the architectural past and the tourism uplift of this city.